THE ROLE OF PATIENT SATISFACTION QUALITY IN MCU PATIENT LOYALTY AT BEKASI PRIVATE HOSPITAL - Nanda Putra; Tantri Yanuar Rahmat Syah; Ratna Indrawati (CV. Bunda Ratu, 2024)
Patient loyalty is an important behavior possessed by patients as users of hospital services. Loyalty patients can benefit the Hospital. Loyalty is obtained as a manifestation of perceived brand image, hospital empathy and patient satisfaction that is obtained from quality service. The purpose of this study was to analyze the relationship between brand image, hospital empathy, patient satisfaction and MCU patient loyalty at X Hospital. This research method uses a quantitative approach, using a cross-sectional design, sampling technique with purposive sampling, with a total sample of 349 respondents. The results of the bivariate analysis, with chi-square analysis, showed that there was a relationship between brand image and patient loyalty, with a p-value (0.000<0.05), there is a relationship between Hospital empathy and patient loyalty, p-value (0.000<0.05) and there is a relationship between patient satisfaction and patient loyalty with a p-value (0.000<0.05). The results of the multivariate analysis showed that the most dominant variable was patient satisfaction with a p-value (0.001) and odds-ratio (2.071). The conclusion in this study is the importance of brand image, hospital empathy and patient satisfaction in creating a loyal patient attitude. Hospital management must evaluate patient loyalty on an ongoing basis, as a basic consideration in developing strategies to provide quality services. The results of the multivariate analysis showed that the most dominant variable was patient satisfaction with a p-value (0.001) and odds-ratio (2.071). The conclusion in this study is the importance of brand image, hospital empathy and patient satisfaction in creating a loyal patient attitude. Hospital management must evaluate patient loyalty on an ongoing basis, as a basic consideration in developing strategies to provide quality services. The results of the multivariate analysis showed that the most dominant variable was patient satisfaction with a p-value (0.001) and odds-ratio (2.071). The conclusion in this study is the importance of brand image, hospital empathy and patient satisfaction in creating a loyal patient attitude. Hospital management must evaluate patient loyalty on an ongoing basis, as a basic consideration in developing strategies to provide quality services. Keywords: Brand Image, Empathy, Satisfaction, Loyalty, MCU.